1997
DOI: 10.1086/514015
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Marker of Preclinical Tuberculosis in Human Immunodeficiency Virus Infection: Antibodies to an 88‐kDa Secreted Antigen ofMycobacterium tuberculosis

Abstract: Antibodies to purified, size-fractionated secreted proteins of Mycobacterium tuberculosis in sera from patients with human immunodeficiency virus (HIV) infection and active tuberculosis (HIV/TB patients), and in stored sera obtained from the same patients prior to clinical manifestation of TB, were evaluated by ELISA, and the repertoire of antigens recognized was analyzed by immunoblotting. Compared with non-HIV/TB patients, HIV/TB patients had lower levels of anti-mycobacterial antibodies, and these were dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 1 publication
2
48
0
Order By: Relevance
“…In the studies most of the polypeptides above 30 kDa showed prominent seroreactivity. It was not surprising to observe greater antibody responses to higher-molecularmass antigens since a direct relationship between molecular mass and antibody response has been reported earlier (8,26,27). To detect possible differences in the specificity of mycobacterial antigens between T lymphocytes from peripheral blood and from the site of infection, we investigated the pleural fluid lymphocyte responses of tuberculous pleurisy patients.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the studies most of the polypeptides above 30 kDa showed prominent seroreactivity. It was not surprising to observe greater antibody responses to higher-molecularmass antigens since a direct relationship between molecular mass and antibody response has been reported earlier (8,26,27). To detect possible differences in the specificity of mycobacterial antigens between T lymphocytes from peripheral blood and from the site of infection, we investigated the pleural fluid lymphocyte responses of tuberculous pleurisy patients.…”
Section: Discussionmentioning
confidence: 60%
“…Attempts to screen human immune responses against these narrow-molecular-mass fractions demonstrate that low-molecular-mass proteins are prominently recognized by T lymphocytes (12,20), while high-molecular-mass proteins are the major targets of B lymphocytes and induce humoral immune responses (26,27). In view of the potential of lowmolecular-mass polypeptides to augment protective cell-medi-ated immune responses in humans, we purified 104 polypeptides (bands) from the low-molecular-mass (Ͻ40 kDa) secretory proteome of M. tuberculosis and evaluated them for recognition by leukocytes from the above-mentioned models of human immunity to TB.…”
mentioning
confidence: 99%
“…This suggests that antibodies to this protein are present in M. tuberculosis-infected individuals who have not yet developed the active disease. Recently, Laal et al [33] have also noted that antibodies to several M. tuberculosis-specific proteins could be detected in the sera of human immunodeficiency virus (HIV)-infected individuals long before they developed the active disease. Our findings clearly indicate the potential of the ORF-14 protein for the development of serodiagnostic tools for specific identification of M. tuberculosis infection and for the distinction between BCG-vaccinated and M. tuberculosis-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A study using ES -38 kDa antigen and anti-ES-38 antibodies have been reported primarily in patients with recurrent advanced chronic TB infection [12]. Laal et al [13] have reported the presence of 88 kDa secreted antigen as a surrogate marker for identifying HIV infected persons with active, subclinical disease who are at the higher risk of developing clinical tuberculosis. A study by Kaplan et al [14] showed difference in antibody levels in patients of new and relapse TB cases using crude culture filtrate antigen by immunodiffusion test.…”
Section: Proteins Released By M Tb Bacilli During Growthmentioning
confidence: 99%